COGNITIVE APPROACHES IN TRANSLATION STUDIES: PROCESSES, MODELS, AND EMPIRICAL INSIGHTS - Sadikova Salima Zoxidovna (American Journals Publishing, 2025)
This article delves into the cognitive dimensions of translation studies, tracing its historical development from process-oriented research in the 1980s to contemporary integrations with neuroscience and technology. It explores key models of bilingual cognition, empirical methodologies like eye-tracking and neuroimaging, and their applications to translation and interpreting processes. Emphasizing cognitive effort, decision-making, and human-machine interactions, the discussion critiques reductionist tendencies while advocating for situated and extended cognition frameworks. The article underscores the field’s contributions to understanding mental mechanisms in translation, with implications for training, ethics, and future technological advancements.
Keywords: Cognitive translation studies, bilingual cognition, think-aloud protocols, eye-tracking, Effort Model, Relevance Theory, machine translation post-editing, situated cognition, neuroimaging in translation, translation process research.